2010
DOI: 10.1155/2010/423087
|View full text |Cite
|
Sign up to set email alerts
|

Typologies of Extreme Longevity Myths

Abstract: Purpose. Political, national, religious, and other motivations have led the media and even scientists to errantly accept extreme longevity claims prima facie. We describe various causes of false claims of extraordinary longevity. Design and Methods. American Social Security Death Index files for the period 1980–2009 were queried for individuals with birth and death dates yielding ages 110+ years of age. Frequency was compared to a list of age-validated supercentenarians maintained by the Gerontology Research G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…This study is primarily concerned with the possibility of incorrect dates reported in family histories. Previous studies demonstrated that age misreporting and age exaggeration in particular are more common among long-lived individuals (Elo et al, 1996; Hill et al, 2000; Jeune and Vaupel, 1999; Rosenwaike and Hill, 1996; Rosenwaike and Stone, 2003; Rosenwaike et al, 1998; Shrestha and Rosenwaike, 1996; Young et al, 2010). Therefore, the primary focus in our study was on the age verification for long-lived individuals.…”
Section: Study 1: Why Centenarians Are Different From Their Shorter-lmentioning
confidence: 99%
“…This study is primarily concerned with the possibility of incorrect dates reported in family histories. Previous studies demonstrated that age misreporting and age exaggeration in particular are more common among long-lived individuals (Elo et al, 1996; Hill et al, 2000; Jeune and Vaupel, 1999; Rosenwaike and Hill, 1996; Rosenwaike and Stone, 2003; Rosenwaike et al, 1998; Shrestha and Rosenwaike, 1996; Young et al, 2010). Therefore, the primary focus in our study was on the age verification for long-lived individuals.…”
Section: Study 1: Why Centenarians Are Different From Their Shorter-lmentioning
confidence: 99%
“…The majority of the NECS centenarians were born between 1880 and 1910 and reached a median survival of 103 years, thus surviving 30–40 years past the median survival of their birth year cohort. Birth certificates were available for only about 30% of the centenarians and therefore US census data from the early 1900s and other techniques were used for validating date of birth (Young et al, 2010; Andersen et al, 2012). Typically, 99% of age claims 115 years and older are false, and therefore in the case of supercentenarians, the NECS takes extra steps to prove a person’s age including family reconstitution and collecting multiple forms of proof that all must be consistent with one another (Young et al, 2010).…”
Section: The New England Centenarian Study and Exceptional Longevitymentioning
confidence: 99%
“…Birth certificates were available for only about 30% of the centenarians and therefore US census data from the early 1900s and other techniques were used for validating date of birth (Young et al, 2010; Andersen et al, 2012). Typically, 99% of age claims 115 years and older are false, and therefore in the case of supercentenarians, the NECS takes extra steps to prove a person’s age including family reconstitution and collecting multiple forms of proof that all must be consistent with one another (Young et al, 2010). Demographic, health, and family history data, as well as physical and cognitive function data are collected at least once for the majority of study subjects and are updated annually for living subjects.…”
Section: The New England Centenarian Study and Exceptional Longevitymentioning
confidence: 99%
“…However, this quest for longevity islands has proved to be problematic. Claims of exceptional longevity in little-developed communities in the Andes and in the Caucasus (Leaf and Launois 1975) did not stand up to systematic scrutiny of the true age of supposed centenarians or supercentenarians (Garson 1991) (Young et al 2010). Demographers are also aware that age exaggeration among the oldest old in censuses leads to substantial age inflation in very old-age populations, and consequently, to underestimated mortality rates at old ages when computed using census-based denominators especially in populations with low levels of literacy (Coale and Kisker 1986; Preston et al 1999).…”
Section: Introductionmentioning
confidence: 99%